A Review of Nutritional Rehabilitation Homes on Child Malnutrition Management and Household Socio-Economic Well-being in Nepal - Khatiwada, Kabita; Thapa, Arjun; Sharma, Bimala (International Research Journal of MMC, 2026)
Background: Childhood malnutrition remains a persistent public health challenge in Nepal, particularly among rural and marginalized populations. Nutritional Rehabilitation Homes (NRHs) and Outpatient Therapeutic Centers (OTCs) have been established to address severe and moderate acute malnutrition (SAM/MAM), yet questions persist regarding long-term sustainability of recovery. Objective: This review comprehensively examines outcomes of nutritional rehabilitation for children in Nepal, focusing on clinical efficacy, socioeconomic determinants, and post-discharge well-being. Methods: A narrative literature review was conducted using Google Scholar, Scopus, and Nepal Journals Online (NEPJOL). Twenty-one studies published between 2000 and 2026 were synthesized thematically. Results: Clinical outcomes in Nepalese NRHs meet international standards, with mean weight gains of 4-7 g/kg/day and case fatality rates between 4-9%. However, a significant "sustainability gap" exists, with poor post-discharge follow-up and limited translation of facility-based gains into long-term recovery. Household socioeconomic status, maternal health literacy, and food security strongly influence outcomes. Emerging evidence supports integrated models combining nutritional treatment with psychosocial stimulation and community-based multisectoral interventions. Conclusion: While nutritional rehabilitation programs in Nepal achieve short-term clinical success, long-term sustainability remains inadequate. Future interventions must address underlying household determinants and integrate nutrition-specific with nutrition-sensitive approaches. Research gaps include longitudinal follow-up studies, economic evaluations of integrated models, and implementation research within Nepal’s federalized health system.